Anlasmali Ögrenme Teknigi Dogrultusunda 6. Sinif Ögrencilerinin Okumaya Yönelik Tercihlerinin Belirlenmesi - Aydin, Rukiye Isik (Istanbul Sabahattin Zaim University, 2023)
Öz
Determining Reading Preferences of 6th Grade Students in the Line of Negotiated Learning Technique
Keywords: Turkish Education; Türkçe Egitimi